Implementation of Discovery Inquiry Learning Model to Improve the Activities and Achievements of Learning Mathematics Materials Reducing Area Formulas Flat Building for Students of Class VI Semester I SD Negeri Jenang 10 2017/2018 Academic Year - Ahmad Latif; Atik Meliani (Proceedings Series on Social Sciences & Humanities, 2023)
The research entitled Application of the Discovery Inquiry Learning Model to Increase Learning Activity and Achievement in Mathematics for the Material of Lowering the Area of a Flat Shape Formula in Class VI Semester I Students of SD Negeri Jenang 10 Academic Year 2017/2018. With research subjects totaling 10 children consisting of 8 boys and 2 girls. This research was conducted because the students' learning achievement was low in pre-cycle conditions with an average value of 55. This research was carried out in two cycles, each cycle using the Discovery Inquiry learning model. Data collection was carried out through questionnaires, tests, and observations. Indicators of success in this study if 85% of students complete learning and show activeness. The results showed an increase in student learning activity from cycle I and cycle II, namely in cycle I achieved a score of 45.5 entered in the good category increased to 55 entered in the very good category in cycle II. The results of student achievement also increased. The results of student achievement in cycle I reached an average of 71.5 and increased in cycle II to 82.5. From the research results. learning completeness increased in cycle I (60%) and in cycle II (100%), there was an increase in learning mastery by (40%). The application of the Discovery Inquiry learning model can increase student learning activities and achievements.